COBIT 2019 for IT Governance Evaluation: A Cross-Sector Systematic Review - Putra, Donas; Siahaan, Andysah Putera Utama (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
IT governance is important because it helps make sure that a company's technology resources work well with its business goals and last for a long time. This study does a thorough review of existing research (called a systematic literature review) to look at how the COBIT 2019 framework is being used in different industries and areas of governance. All the chosen studies were looked at and sorted into groups based on the type of organization, the COBIT 2019 areas, and the goals of governance. The results show that COBIT 2019 is used in many different areas, like education, government, healthcare, industry, and companies that operate in the digital marketplace. The most common areas that come up are Align, Plan and Organize (APO), Build, Acquire and Implement (BAI), Deliver, Service and Support (DSS), and Evaluate, Direct and Monitor (EDM). Among these, the DSS and APO domains are most common as generaly.